Sewage disposal at ice cap installations, project 15 - Bader, Henri, 1907-; Small, F. A., author.; U.S. Army Snow, Ice, and Permafrost Research Establishment. (Wilmette, Ill. : Snow Ice and Permafrost Research Establishment, Corps of Engineers, U.S. Army, 1955)
"April, 1955"--Cover. Caption title. Mode of access: Internet.